Mobile phone design and it's impact on customer's affective experience: Two country comparison - Seva, Rosemary R. (Animo Repository, 2007)
Affective product design is a new area of interest in the human factor field. Products are known to elicit emotional responses from consumers. However, it is not known if emotion is elicited by product attributes because previous research have not established the relationship between physical attribute and emotion. This study aims to predict emotional responses from product design attributes and relate these emotional responses to consumer's intention to buy the product. A field study was conducted in two countries, namely; Singapore and Philippines. Emotional responses to mobile phone design were compared and results suggest that different product attributes elicit emotions for the two countries suggesting uniqueness in preferences. Pre-purchase affect is also a significant predictor of purchase intention. Product designers can benefit from this study by identifying product characteristics that they should focus on to enhance affect and purchase intention.